2021
DOI: 10.1371/journal.pmed.1003854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of healthcare avoidance during the COVID-19 pandemic: A population-based cross-sectional study

Abstract: Background During the Coronavirus Disease 2019 (COVID-19) pandemic, the number of consultations and diagnoses in primary care and referrals to specialist care declined substantially compared to prepandemic levels. Beyond deferral of elective non-COVID-19 care by healthcare providers, it is unclear to what extent healthcare avoidance by community-dwelling individuals contributed to this decline in routine healthcare utilisation. Moreover, it is uncertain which specific symptoms were left unheeded by patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 29 publications
12
77
2
4
Order By: Relevance
“…Similar to previous studies [37,38], our study found that adolescents and young adults with an ongoing illness were more likely to avoid healthcare than those without any illness. This effect was amplified during the COVID-19 pandemic and could be attributed to a concern of contracting COVID-19, given the greater risk of poorer outcomes for COVID-19 in individuals with comorbidities [61].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies [37,38], our study found that adolescents and young adults with an ongoing illness were more likely to avoid healthcare than those without any illness. This effect was amplified during the COVID-19 pandemic and could be attributed to a concern of contracting COVID-19, given the greater risk of poorer outcomes for COVID-19 in individuals with comorbidities [61].…”
Section: Discussionsupporting
confidence: 90%
“…This gap has been significantly narrowed during the pandemic period, suggesting that elective interventions were mainly postponed. These Hungarian observations are not in line with the independence between education and HCU during the pandemic, as described in the EU [ 23 ] and the Netherlands [ 46 ], but these results were similar to the main findings of the SHARE Corona Survey on 27 European countries’ 50+ year-old populations [ 41 ]. Furthermore, our investigation demonstrated the inverse relationship of CRPNR with education, which was exaggerated in the pandemic period.…”
Section: Discussionsupporting
confidence: 45%
“…This gap has been significantly narrowed during the pandemic period, suggesting that elective interventions were mainly postponed. These Hungarian observations are not in line with the independence between education and health care use during the pandemic, as described in the EU [29] and in the Netherlands [50], but these results were similar to the main findings of the SHARE Corona Survey on 27 European countries' 50+ year-old population [45]. Furthermore, our investigation demonstrated the inverse relationship of CRPNR with education, which was exaggerated in the pandemic period.…”
Section: Pandemic Impact By Level Of Educationsupporting
confidence: 59%